Evaluasi Penggunaan Antibiotik pada Pasien Dewasa Rawat Inap di Puskesmas Sumbersari Jember dengan Metode ATC/DDD 2018 - Zaenudin, Mohamad Nor; Rachmawati, Ema; Rachmawati, Sinta (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Antibiotics are the most widely used drugs for bacterial infectious diseases. Irrational use of antibiotics affects the increase in morbidity and mortality, resistance, and cost burden. One method that can be used to overcome the problem of resistance is to evaluate the use of antibiotics. This study aims to evaluate the use of antibiotics in the Sumbersari Puskesmas in 2018 which was conducted quantitatively using the ATC / DDD (Anatomical Therapeutic Chemical / Defined Daily Dose) method. This study uses a cross-sectional descriptive study with retrospective data on adult patients undergoing hospitalization. Data on antibiotic use was obtained from 455 medical records for the 2018 period. Data taken included patient profiles, diagnosis, and antibiotic prescribing. The quantity of antibiotic use was calculated by the DDD 100 patient-days formula and analyzed descriptively. The results showed that the disease most commonly suffered by adult patients was typhoid (30.5%). Besides, there are 7 types of antibiotics prescribed with a total DDD value of 36.93 DDD / 100 patient-days. The highest DDD value is ceftriaxone with a DDD value of 16.90 DDD / 100 patient-days.